A REVIEW ON PHARMACOLOGY AND THERAPEUTIC EFFECTS OF EMPAGLIFLOZIN IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - CHADEVE, AJAY (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Empagliflozin, a sodium glucose cotransporter 2 inhibitor, a newer class of antihyperglycemic agent, which offers the convenience of once-daily oral administration and carries a low inherent risk of hypoglycemia as a result of its unique mechanism of action, enabling it to be used as monotherapy and as an adjunct with other antidiabetic drugs. Empagliflozin has a unique mechanism of action by inhibiting glucose and sodium reabsorption in the proximal tubule of the kidney; they induce urinary glucose excretion and natriuresis. In patients with diabetes, empagliflozin results in glucose lowering, blood pressure (BP) reduction and weight loss. Empagliflozin reduced cardiovascular morbidity and mortality in patient with type 2 diabetes mellitus and established cardiovascular disease in the EMPA-REG OUTCOME trial®. The recommended starting dosage of empagliflozin is 10 mg daily. The dosage may be increased to a maximum of 25 mg/day in patients tolerating empagliflozin 10 mg/day. The most common adverse effect observed with empagliflozin (sodium glucose cotransporter 2 inhibitors) is an increment in mycotic genital infections. In this review article, we discussed the pharmacological properties, therapeutic effects, and adverse events that are associated with the administration of empagliflozin in patients with type 2 diabetes mellitus. In conclusion, empagliflozin provides greater therapeutic benefits in the management of type 2 diabetes mellitus and reduce the associated cardiovascular risk factors such as blood pressure (BP) and weight.